Leaf Induction Impacts Behavior and Performance of a Pollinating Herbivore - Jacobsen, Deidra J.; Raguso, Robert A. (Frontiers in Plant Science, 2021)
Flowering plants use volatiles to attract pollinators while deterring herbivores. Vegetative and floral traits may interact to affect insect behavior. Pollinator behavior is most likely influenced by leaf traits when larval stages interact with plants in different ways than adult stages, such as when larvae are leaf herbivores but adult moths visit flowers as pollinators. Here, we determine how leaf induction and corresponding volatile differences in induced plants influence behavior in adult moths and whether these preferences align with larval performance. We manipulated vegetative induction in four Nicotiana species. Using paired induced and control plants of the same species with standardized artificial flowers, we measured foraging and oviposition choices by their ecologically and economically important herbivore/pollinator, Manduca sexta. In parallel, we measured growth rates of M. sexta larvae fed leaves from control or induced plants to determine if this was consistent with female oviposition preference. Lastly, we used plant headspace collections and gas chromatography to quantify volatile compounds from both induced and control leaves to link changes in plant chemistry with moth behavior. In the absence of floral chemical cues, vegetative defensive status influenced adult moth foraging preference from artificial flowers in one species (N. excelsior), where females nectared from induced plants more often than control plants. Plant vegetative resistance consistently influenced oviposition choice such that moths deposited more eggs on control plants than on induced plants of all four species. This oviposition preference for control plants aligned with higher larval growth rates on control leaves compared with induced leaves. Control and induced plants of each species had similar leaf volatile profiles, but induced plants had higher emission levels. Leaves of N. excelsior produced the most volatile compounds, including some inducible compounds typically associated with floral scent. We demonstrate that vegetative plant defensive volatiles play a role in host plant selection and that insects assess information from leaves differently when choosing between nectaring and oviposition locations. These results underscore the complex interactions between plants, their pollinators, and herbivores.